2010
DOI: 10.3844/jssp.2010.320.323
|View full text |Cite
|
Sign up to set email alerts
|

The Buddha Images and Conservation and Adherence to Cultural Values in Northeast

Abstract: Problem statement: Buddha image is a symbol which built for representing the Buddha. At present, the majority of people always misinterpret and misevaluate the real value of Buddha image. As a matter of fact, Buddha image enhances social solidarity and social networks of Northeast-Thai people. Appreciating value of Buddha image is necessary for next generation so a study of Buddhist Philosophy towards Buddha images and current problems concerning interpretation and evaluation is a serious study. This research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…These things will be able to increase faith in Buddhism. They are increasing the belief that there are real karma, increasing the belief that there are real effects of karma, increasing the belief that world creatures have karma of their own, increasing the belief in the Lord Buddha's intelligences in enlightenment and the listeners to preaching still have faith in the Three Gems, namely the Buddha, the Dharma and the Sangha (Suksri et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…These things will be able to increase faith in Buddhism. They are increasing the belief that there are real karma, increasing the belief that there are real effects of karma, increasing the belief that world creatures have karma of their own, increasing the belief in the Lord Buddha's intelligences in enlightenment and the listeners to preaching still have faith in the Three Gems, namely the Buddha, the Dharma and the Sangha (Suksri et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The findings are as follows: Suksri et al (2010), he studied about "The Buddha Images and Conservation and Adherence to Cultural Value in Northeast". It revealed that there were 5 models of the Buddha image art found in Isan: Sandstone Buddha images, bakedclay votive tablets, cast motar Buddha images, bronze Buddha images and wooden Buddha images.…”
Section: Resultsmentioning
confidence: 99%
“…It is serious and critical that people stay away from temples, no ethics and morality in educational curriculum and disunity in families. In this situation, therefore, government must have distinct policies by utilizing Buddhist Dhamma to solve those problems and to develop the country for further prosperity" (Suksri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mass media was a two-edged sword. If they had not good judgment they would copy bad things, so parents should pay more attention on this matter (Suksri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%